Technique and algorithms for induction electromotive loading node stability assessment of oil fields at three-phase unbalance voltage sag - F. A. Losev; V. V. Sushkov (Омский научный вестник)
The main aim of the research is stability assessment of induction electromotive loading node at to three-phase unbalance voltage sag. The authors developed a technique and algorithms of loading node stability assessment on the basis of mathematical model of an induction motor, the transformer and the line for a positivesequence network and a negative sequence network. The modeling results showed that voltage increase in a negative sequence leads to decrease a stability reserve of induction electromotive loading node.